Green Growth or Economic Gain? Assessing Environmental Efficiency Using Data Envelopment Analysis: Case of Africa - Ikram, Benomar; Mariame, Ababou (International Journal of Energy Economics and Policy, 2024)
In the African context, achieving sustainable development while fostering economic growth and environmental conservation presents a formidable challenge. This article employs Data Envelopment Analysis (DEA) to assess the environmental efficiency of 34 African countries from 2013 to 2022. Using key economic indicators such as Foreign Direct Investment (FDI), Logistics Performance Index (LPI), and Gross Domestic Product (GDP) relative to CO2 emissions, the study evaluates the ability of African nations to optimize economic output while minimizing environmental impact. The analysis reveals significant heterogeneity in environmental efficiency levels among countries, with some demonstrating high efficiency, while others exhibit room for improvement. Factors such as FDI, LPI, and GDP play pivotal roles in shaping environmental outcomes, highlighting the need for sustainable investment practices and infrastructure development. Peer comparison and output slack analysis provide further insights, identifying opportunities for enhancing efficiency and promoting sustainable growth. Case studies of South Africa, Mali, and Zambia underscore varying degrees of environmental efficiency and offer valuable lessons for sustainable development across the continent. Overall, the findings contribute to a deeper understanding of environmental efficiency in Africa and provide a roadmap for policymakers to pursue greener and more inclusive development trajectories.